The Impact of the Development Trend and Policy Optimi-zation of NEV on Guizhou Consumers' Usage Behavior Based on Its Natural Environment - Yee Fai Fred Cheng; Jacky Mong Kwan Watt (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Hong Kong's well-established financial platform has become a key driver of the international expansion of small and medium-sized enterprises (SMEs) from mainland China. This article examines how Hong Kong's financial ecosystem—including capital-raising channels, trade finance, supply chain financing, investment facilitation, corporate governance frameworks, and global market access—supports SME growth and internationalization. The analysis identifies the types of SMEs that benefit most from these financial services, the primary purposes of the funds obtained, the organizational requirements for accessing financing, the advantages of establishing companies in Hong Kong, and the financing options available, including government-backed loans, initial public offerings (IPOs), and private financing markets. The findings indicate that Hong Kong's financial platform effectively reduces financing constraints, improves cross-border business efficiency, strengthens corporate governance practices, and enhances international competitiveness. In addition, the platform provides SMEs with greater credibility and access to global investors and business networks. The study concludes that leveraging Hong Kong's financial infrastructure can significantly accelerate the international growth of mainland Chinese SMEs and recommends strategic collaboration between enterprises and policymakers to maximize these financial and institutional advantages.